Existence of periodic solutions in the modified Wheldon model of CML - Amster, Pablo Gustavo (2013)
The Wheldon model (1975) of a chronic myelogenous leukemia (CML) dynamics is modified and enriched by introduction of a time-varying microenvironment and time-dependent drug efficacies. The resulting model is a special class of nonautonomous nonlinear system of differential equations with delays. Via topological methods, the existence of positive periodic solutions is proven. We introduce our main insight and formulate some relevant open problems and conjectures.